Gangguan cemas pada Penderita Gastroesophageal Reflux Disease (GERD) Berdasarkan Pendekatan Surah Al-Insyirah (94: 1-8): (Sebuah Perpaduan Perspektif Psikologi dan Al-Qur'an) - Riyanda Utari; Novy Yulianty; Anggi Anggraeni (Bayani: Jurnal Studi Islam, 2026)
Gastroesophageal Reflux Disease (GERD) is a digestive system disorder that not only causes physical problems but is also closely related to an individual’s psychological condition, particularly anxiety disorders. Recurrent GERD symptoms such as heartburn, chest burning sensation, shortness of breath, nausea, and physical discomfort can trigger fear, excessive worry, and emotional distress in sufferers. This condition indicates the existence of a psychosomatic relationship between physical and psychological disorders. This study aims to analyze anxiety behavior in GERD sufferers based on psychological perspectives and the approach of Surah Al-Insyirah verses 1–8 as an integration of psychology and Qur’anic perspectives. This study employed a literature review method with a descriptive qualitative approach. Data were obtained through various scientific sources, including national and international journals, academic books, research articles, and Qur’anic interpretation studies relevant to the research topic. Data analysis was conducted using content analysis by reviewing, comparing, and interpreting theories and previous studies related to GERD, anxiety disorders, Islamic psychology, and the psychological values contained in Surah Al-Insyirah. The results of the study indicate that anxiety disorders in GERD sufferers are influenced by a bidirectional relationship between physical and psychological conditions. Anxiety may worsen GERD symptoms through stress responses and increased body sensitivity to pain, while recurring GERD symptoms can increase fear and excessive concern about health conditions. From the perspective of Islamic psychology, spiritual approaches such as dhikr (remembrance of Allah), tawakal (trust in God), patience, and positive thinking toward Allah (husnuzan) can help individuals achieve inner peace and improve emotional regulation. Furthermore, Surah Al-Insyirah verses 1–8 contain psychological values such as optimism, mental strengthening, resilience, and the belief that every hardship is accompanied by ease. These values are consistent with the concept of cognitive reframing in modern psychology. Based on the findings, it can be concluded that the integration of psychological perspectives and Qur’anic values, particularly Surah Al-Insyirah verses 1–8, can serve as a holistic approach in understanding and helping overcome anxiety disorders in GERD sufferers. This approach not only focuses on physical and psychological conditions but also emphasizes the spiritual aspect as an essential component of mental health.